2016
DOI: 10.3892/ol.2016.4653
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA are aberrantly expressed in human papillary thyroid carcinoma

Abstract: Long noncoding RNAs (lncRNAs) have emerged as key regulatory molecules at almost every level of gene expression regulation. The altered expression of lncRNAs is a characteristic of numerous types of cancer, and lncRNAs have been demonstrated to promote the development, invasion and metastasis of tumors through various mechanisms. However, the role of lncRNAs in papillary thyroid carcinoma (PTC) remain unclear. In the present study, differentially expressed lncRNAs and mRNAs were detected by human lncRNA microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Numerous studies have demonstrated the superiority of lncRNA as diagnostic and predictive biomarkers in a diverse range of cancers compared to mRNAs and miRNAs (Zhou et al, 2015c(Zhou et al, , 2017(Zhou et al, , 2019Zhou M. et al, 2018b). Aberrant lncRNA expression has also been observed in the development and progression of THCA (Yang et al, 2016;Lu et al, 2018), and several lncRNA biomarkers have been identified for THCA diagnosis and prognosis (Li et al, 2017;Liu et al, 2018;Liang and Sun, 2019). Emerging evidence has shown that DNA methylation is an important epigenetic regulator of lncRNA expression and epigenetic changes in DNA methylation can disturb the expression pattern of lncRNAs and contributes to carcinogenesis (Heilmann et al, 2017;Tang, 2018;Zhou Z. et al, 2018;Bao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the superiority of lncRNA as diagnostic and predictive biomarkers in a diverse range of cancers compared to mRNAs and miRNAs (Zhou et al, 2015c(Zhou et al, , 2017(Zhou et al, , 2019Zhou M. et al, 2018b). Aberrant lncRNA expression has also been observed in the development and progression of THCA (Yang et al, 2016;Lu et al, 2018), and several lncRNA biomarkers have been identified for THCA diagnosis and prognosis (Li et al, 2017;Liu et al, 2018;Liang and Sun, 2019). Emerging evidence has shown that DNA methylation is an important epigenetic regulator of lncRNA expression and epigenetic changes in DNA methylation can disturb the expression pattern of lncRNAs and contributes to carcinogenesis (Heilmann et al, 2017;Tang, 2018;Zhou Z. et al, 2018;Bao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Like proteins, mRNAs and miRNAs, lncRNAs are emerging as novel molecular biomarkers for early diagnosis and prognosis prediction in various cancers [ 12 20 ]. Most recently, thousands of lncRNAs were found to be differentially expressed between PTC and adjacent noncancerous samples [ 21 ]. Another study performed by Lan et al .…”
Section: Introductionmentioning
confidence: 99%
“…P value of TCONS_00024700, NR_028494, ENST00000462717 and ENST00000415582 was < 0.001, <0.001, <0.001 and 0.035,respectively. lncRNAs respectively, which lay the foundation for further investigation of lncRNAs related to PTC [26,27]. In addition, important regulatory mechanisms of lncRNAs in the process of tumorigenesis, progression, proliferation, metastases, apoptosis and autophagy of PTC have been reported [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%